Quality of life and psychological symptoms for women with bipolar disorder – a comparison between reproductive, menopause transition and post-menopause phases. (January 2021) - Perich, Tania; Ussher, Jane; Fraser, Isabel; Perz, Janette
Highlights: Quality of life was lower for women with bipolar disorder during the menopause transition compared with other life stages. Although depression symptoms were similar in post-menopause and menopause transition phases, women during the menopause transition were more likely to report being constantly depressed compared with women at other reproductive stages. Anxiety symptoms were significantly worse for women with bipolar disorder in menopause transition and post-menopause phases compared with reproductive life stages. Abstract: Objective: The menopause transition may be associated with increased symptoms for women living with bipolar disorder; however, few have explored how this compares with other reproductive phases. The aim of this study was to compare women at reproductive, menopause transition and post-menopause phases on measures of quality of life and psychological symptoms associated with bipolar disorder. Study design: Women with bipolar disorder took part in a large international survey conducted online and were categorised into reproductive stages using the STRAW and Monash criteria. The 498 participants were divided into three groups: 202 (41%) in the reproductive age group, 101 (20%) in the menopause transition group and 195 (39%) in the post-menopause group. Main outcome measures: The Menopause Rating Scale (MRS), the Depression Anxiety and Stress Scales – 21 (DASS-21), the Altman Mania Rating Scale (ASRM) and the Bipolar Disorder Quality of Life scale (BD-QoL). Results: BD-QoL scores were significantly lower in the menopause transition group than in the other groups and that group was more likely to report being constantly depressed over the past year than the other groups. Anxiety was significantly higher in the menopause transition and post-menopause groups compared with the reproductive age group. Conclusions: Quality of life and depression are impacted by the menopause transition for women with bipolar disorder. However, anxiety may be a clinical issue for women in both the post-menopause and the menopause transition phases. Research is needed to determine how symptoms vary across the reproductive life cycle for women with bipolar disorder and if targeted treatments may assist.